Media and violence in the Chilean transition - Sunkell, Guillermo (1994)
This study examines the relationship between means and violence at the level of political debate and information content. The work has three central sections. The first examines how the debate on media and violence has been constructed in the period following the installation of the democratic government, identifying the approaches of the main actors that have intervened in its development. The second section analyzes the main features of the media coverage that the mass media have given to the subject of violence. The third section examines the elements of "information" and "entertainment" that are present in the news about crime and terrorist events.